Prescriber opioid patterns following cesarean section pre and post provider training - Alexa Cohen; Melissa J. Fazzari; Gayatri Nangia; Talitha L. Bruney (Clinical and Experimental Obstetrics & Gynecology)
Background: Opioid abuse continues to be an ongoing issue in the United States. Prescriber prescriptions play a large role in this epidemic. This study describes opioid prescribing patterns following cesarean section before and after the New York State Department of Health (NYSDOH) mandated the Opioid Prescriber Training Program in 2017. Methods: This is a retrospective cohort study of 1494 women hospitalized for cesarean section at a single institution in New York City between July 2016 and August 2018. We obtained patient data via chart review. Results: Primary outcome was total amount of opioid prescribed before and after the Opioid Prescriber Training. Secondary outcomes included outpatient opioid prescription habits by provider level, as well as outpatient opioid prescription patterns related to the amount of inpatient opioid use; and patient, surgical, and hospital-specific factors. There was a significant difference in opioids prescribed before and after training. The median dose of opioid prescribed pre and post intervention was 150 morphine milligram equivalents (MME) which is equal to 20 pills of 5 mg of oxycodone. Pre-training, 41.1% of prescriptions amounted to >150 MME, compared with 21.3% post-training (p-value for association <0.001). Post-training, all provider levels had reduced opioid prescriptions in the category of >150 MME. Neither inpatient opioid use, patient demographic, surgical nor hospital factors affected opioid prescriber patterns. Conclusion: This suggests that the NYSDOH mandated opioid training course may have contributed towards changing opioid prescribing patterns with the greatest impact noted in resident physicians.